Sternal Aspiration of Bone Marrow in Dogs: A Practical Approach for Canine Leishmaniasis Diagnosis and Monitoring. (28th September 2013) - Paparcone, Rosa; Fiorentino, Eleonora; Cappiello, Silvia; Gizzarelli, Manuela; Gradoni, Luigi; Oliva, Gaetano; Foglia Manzillo, Valentina
Abstract : Bone-marrow aspirate material is commonly considered as one of the most sensitive tissues for a reliable diagnosis of leishmaniasis. The procedure herein described may permit less experienced veterinarians to be familiar with a quick and safe assessment method for leishmaniasis diagnosis in their patients. Animals are positioned in right lateral recumbency, and the area corresponding to the second, third, or fourth sternebra is identified and aseptically prepared. A 18-gauge needle connected to a 10 mL syringe is driven through the skin, up to the bone wall, and firmly pushed forward while rotating. Entry into the sternebra's cavity is clearly perceived by the fall of resistance offered by the cortex. Some 2, 500 sternal bone-marrow samplings were safely and efficiently performed on 887 dogs of different breeds and aging from 6 months to 14 years, during eight years of clinical activity for routine diagnosis of canine leishmaniasis in pets or for the efficacy evaluation of anti- Leishmania immunobiologicals in dogs naturally exposed to parasite transmission. Most of the samples (1716) were from 387 dogs enrolled for anti- Leishmania vaccine studies. The safety of the method was particularly assessed on these dogs that as per study protocol were submitted to repeated bone-marrow aspirations (2–4 per year) in follow-up examinations.